PEMBUATAN PROFILISASI DUSUN - Yulianto Purwono Prihatmaji (Asian Journal of Innovation and Entrepreneurship, 2013)
The availability of data is valid, reliable and accountable is an important element inthe planning of programs- community development and empowerment. But thephenomenon has been demonstrated that the publication of data on rural / urbanneighborhoods conducted by various agencies are often less accurate and different-different, and not well integrated so that people get confused where the data is accurate.On the other hand the government is not responsive in implementing administrativeprofile data so that data collection activities, training of village profiles become lessperfect, and even neglected. Even the local government there that do not care about thevillage profile data. Based on the findings in the field showed that in Krajan village stilldoes not have a profile or publication so there are still many people who do not knowhow and potential in the hamlet KrajanKrajan village. The purpose of this program is tointroduce the area more about the circumstances, conditions and the potential thatexists in the village. Making this village profiling can be used every person who wants toknow the hamlet of Krajan and the potential that exists in the hamlet Krajan. So it canbe the view and materials for residents to develop the village and the existing potentialso that the village and the residents can be more advanced. The program is carried outwith a couple of stages, conducting interviews and searching for information tocommunity leaders in the village Krajan about the state of society and the potential thatcan be tapped to become the manufacture of profiling. Furthermore shooting and do adescription, the latterdid manufacturing output such as posters and brochures whichcan be used by anyone who wants to know Krajan village. While the result is the profilehamlet / village posters that can be seen so that any newcomer can describe thecondition of the hamlet Krajan.